Relationship between Testosterone levels with Hand Grip Strength, Calf Diameter, Lung Function, Body Mass Index and Blood Pressure in Elderly Men - E.A. Datau; Kenly Kenly; E. Jim; E. Surachmanto; J. Soekarno; I. Lontoh; E. Hadinata (Ridwan Institute, 2023)
The elderly population in Indonesia is increasing every year. Aging is associated with loss and decline in testosterone levels in elderly men. Testosterone deficiency is associated with decreased body mass, decreased bone density, decreased physical function and activity, decreased cognitive function, increased fat mass, increased depressive symptoms and increased risk of falls and fractures. Muscle mass is the largest tissue which covers 40%-50% of the body. To assess muscle strength, hand grip strength can be measured and to assess muscle mass, anthropometric measurements can be made, especially calf diameter. While for body fat can be measured body mass index. The age-related decrease in skeletal muscle mass also affects respiratory muscle function which can be seen from the decline in lung function (FEV1 and FVC). In addition, increased blood pressure is also common in elderly people. Objective: To determine the relationship between the hormone testosterone with hand grip strength, calf diameter, lung function, body mass index (BMI) and blood pressure in elderly men. Method: This study is observational analytic with a cross-sectional study design conducted in Manado on elderly men. Results: From this study, 38 samples of elderly men were obtained who had a significant positive relationship between testosterone levels and FVC values (p = 0.004). There was a significant positive relationship between testosterone levels and the strength of the right-hand grip (p = 0.245) and left-hand grip (p = 0.354), the same was true for FEV1 values (p = 0.078) and systole (p = 0.340) and diastole (p = 0.216). In this study there was a significant negative relationship between testosterone levels with the diameter of the right calf (p = 0.009) and left (p = 0.009) and the same thing also in the BMI value (p = 0.003). Conclusion: The better the testosterone level, the better the FVC value, while the lower the testosterone level, the greater the calf diameter and BMI. FEV1 values, hand grip strength and blood pressure were not significantly affected by testosterone levels.